Física médica e suas aplicações: uma abordagem para o ensino médio - PINTO, Wagner Henry Cabral (2024)
This paper discusses the importance of applied physics in the area of medicine for society, considering that it is important to know that this branch of science is present in various situations of the social context: from a simple x-ray to more modern and complex exams using as an example nuclear medicine for cancer treatment. Thus, this paper entitled Medical Physics and its applications: an approach to high school, was based on the assumptions of Sampaio and Calçada (2005), Chaves et al (2005), Carron and Guimarães (2002), Nersissian (2012) among others. authors. Therefore, the bibliographic survey was used as a method, since it was not necessary to go to the field. After reviewing the readings, it was understood the need for such study in view of the didactic relationships of physics in everyday life, given that the dissemination of such knowledge about what is medical physics, solves the guiding question of how such a strand can be observed on a daily basis by high school students?